Case study of cervical cancer prevention in two sub-Saharan African countries: Rwanda and Sierra Leone - Bangura, Mohamed S.; Zhao, Yuqian; Gonzalez Mendez, Maria Jose; Wang, Yixuan; Didier Sama, Salah; Xu, Kunpeng; Ren, Ran; Ma, Li; Qiao, You-Lin (Frontiers in Medicine, 2022)
Background Cervical cancer is a public health issue of global concern. It is a preventable disease but continues to threaten the lives of women mostly in developing countries in sub-Saharan Africa. Method We selected two Africa countries in sub-Saharan Africa (The Republic of Rwanda and The Republic of Sierra Leone) to show good example of cervical cancer prevention and constrains hindering countries from effectively implementing cervical cancer programs. Secondary data was collected from the World Health Organization (WHO), the International Agency for Research on Cancer (IARC), the Global Burden of Cancer (Globocan), United Nations Development Programme (UNDP), World Bank, and from official websites of the selected countries. A descriptive analysis method was used to source data and compare variables such as the associated factors, disease burden, prevention programs, health workforce, success factors and challenges. Results Rwanda achieved 93.3% human papillomavirus (HPV) vaccination of the three doses of vaccinating girls in class six, as a result of effective school-based platform delivery system and community partnership to figure out girls that are out of school. Rwanda reduced the historical two-decade gap in vaccine introduction between high-and low-income countries. The country also introduced a nationwide cervical cancer screening and treatment programme. An impressive decreased cervical cancer incidence rate in Rwanda in recent years was observed. Sierra Leone lags behind in terms of almost all cervical cancer prevention programs. Therefore, Sierra Leone needs more efforts to implement cervical cancer intervention programs at national level, including the HPV vaccination, train and increase the number of health professionals, treatment and palliative care services to accelerate cervical cancer activities. Conclusion The disease burden of cervical cancer for Rwanda and Sierra Leone are heavy. There remains a huge room for improvement in preventing and controlling cervical cancer in these countries. The goal of cervical cancer elimination would not be feasible in countries without the awareness and will of the policymakers and the public, the compliance to fund cervical cancer programs, the prioritization of cervical cancer activities, the availability of resources, the adequate health workforce and infrastructure, the cross-sectional collaboration and planning, inter-sectorial, national, regional and international partnerships.